Death Receptor Fas as Molecular Target of Soursop Leaves Novel Isolate in Liver Cancer Targeted Therapy - Maya Tejasari; Dwi Prasetyo; Siti Aminah Abdurachman; Herri S. Sastramihardja (Global Medical & Health Communication (GMHC), 2020)
In the past few decades, no effective systemic therapeutic modalities established in the unresectable liver cancer stage, so the prognosis remains poor. Apoptotic dysregulation of cancer cells through Fas gene expression linked to tumor development, progression, and resistance to treatment. Soursop plants believed to have potent anticancer activity. It hypothesized that active compounds in the soursop leaves would induce apoptosis by interfering with Fas gene expression in liver cancer cells. The study objective was to explore the role of an isolated from soursop leaves against Fas gene expression in liver cancer cells. This study used the HepG2 cell line culture, and treatment groups were given novel isolate (SF-1603) from soursop leaves with three different doses which conducted in Bandung in 2017. Observations assessed in hours 0, 24, 48, and 72. Measurement of gene expression was done with real-time PCR and apoptosis detection by the TUNEL method. The results showed that the novel isolate (SF-1603) from soursop leaves stimulate Fas optimum expressions to initiate apoptosis with 0.5×inhibitory concentration 50 (IC50) dosage at observation hour 48. There was a strong correlation between Fas gene expression with the apoptosis level. It concluded that the novel isolate (SF-1603) from soursop leaves is a potent anticancer that affects Fas gene expression in apoptosis induction on the liver cancer cell. It can be used as a candidate for a new therapeutic agent for liver cancer treatment. RESEPTOR FAS SEBAGAI SASARAN MOLEKULER NOVEL ISOLAT DAUN SIRSAK PADA TERAPI BERTARGET KANKER HATIDalam beberapa dekade terakhir, tidak ada modalitas terapi sistemik yang efektif untuk pengobatan kanker hati tahap lanjut sehingga prognosisnya buruk. Disregulasi apoptosis sel kanker melalui ekspresi gen Fas terkait dengan perkembangan, perkembangan tumor, dan resistensi terhadap pengobatan. Tanaman sirsak dipercaya memiliki aktivitas antikanker yang kuat. Senyawa aktif dalam daun sirsak secara hipotesis dapat menginduksi apoptosis dengan memengaruhi ekspresi gen Fas pada sel kanker hati. Tujuan penelitian adalah mengeksplorasi peran isolat daun sirsak terhadap ekspresi gen Fas pada sel kanker hati. Penelitian ini menggunakan kultur sel kanker HepG2 dan kelompok perlakuan diberi isolat baru (SF-1603) daun sirsak dengan 3 dosis berbeda. Pengamatan dinilai pada jam ke-0, 24, 48, dan 72. Pengukuran ekspresi gen dilakukan dengan PCR real-time dan deteksi apoptosis dengan metode TUNEL. Hasil penelitian menunjukkan bahwa novel isolat (SF-1603) daun sirsak menstimulasi ekspresi optimal Fas untuk inisiasi apoptosis dengan dosis 0,5×inhibitory concentration 50 (IC50) pada pengamatan 48 jam. Terdapat korelasi yang kuat antara ekspresi gen Fas dan tingkat apoptosis. Disimpulkan bahwa isolat baru (SF-1603) daun sirsak adalah antikanker kuat yang memengaruhi ekspresi gen Fas dalam induksi apoptosis pada sel kanker hati sehingga dapat digunakan sebagai kandidat agen terapi baru untuk pengobatan kanker hati.